Evaluation of Mechanical and Wear Properties of Aluminium AA430 Reinforced with SiC and Mgo. (2017) - Mohan Kumar, S.; Pramod, R.; Govindaraju, H.K.
Abstract: Aluminum metal matrix composites (MMC's) are very widely used for several different applications like Aerospace, Automotive and Marine industries owing to their unique properties. While fabricating Hybrid MMC's using stir casting technique several technical challenges exist like achieving a uniform distribution of reinforcement within the matrix during stir casting which affects material behavior. Aluminum (AA 443.0) and SiC + MgO has been chosen as matrix and reinforcement material respectively. Experiments have been conducted by varying weight fraction of SiC + MgO (2.5%, 5% and 7.5%) while keeping all other parameters constant. An increasing trend of hardness and tensile strength with increase in weight percentage of SiC+MgO has been observed. The results also reveal that the wear rate of the test specimen's increase with the increasing load and sliding distance. The coefficient of friction slightly decreased with increasing volume content of reinforcement.